Atomic atmosphere: a way to understand phase evolution during vanadium slag roasting at the atomic level. Issue 6 (6th November 2019) - Li, Hong-Yi; Wang, Kang; Wang, Chengjie; Lin, Minmin; Xie, Bing
Abstract : The concept of `atomic atmosphere' is proposed, which includes chemical state, chemical and spatial environments, to uncover the atomic level reaction mechanism of crystal‐involved solid reactions. Abstract : To increase vanadium recovery, it is critical to understand the intrinsic phase evolution during vanadium slag roasting. This work proposes the novel concept of `atomic atmosphere' to effectively evaluate and recognize the microscopic state of the vanadium atom in vanadium slag before and after roasting. Atomic atmosphere includes the chemical state, chemical environment and spatial environment of the atom, and provides a universal way to explore the microscopic phase evolution mechanism during the metal‐extraction process from minerals.